Metabolite Profile Evaluation of Indonesian Roasted Robusta Coffees by 1H NMR Technique and Chemometrics - Nizar Happyana; Elvira Hermawati; Yana Maolana Syah; Euis Holisotan Hakim (Indonesian Journal of Chemistry, 2020)
In this work, 1H NMR analysis, along with a chemometrics approach, had been applied for investigating metabolite profiles of Indonesian roasted Robusta coffees obtained from Lampung and Aceh. In total, 24 compounds had been successfully detected in the 1H NMR spectra of the Robusta coffee extracts. Concentrations of some identified metabolites present in the coffees were determined by the quantitative 1H NMR technique. Orthogonal projection to latent structure-discriminant analysis (OPLSDA) was used as a primary method for the chemometric approach. OPLSDA had classified clearly the Robusta coffee samples corresponding to their origin. Loading plot and S-plot of the OPLSDA revealed characteristic metabolites for each Robusta coffee. The results indicated that quinic acid, mannose, arabinoses, and acetic acid were an important discriminant compound for Lampung Robusta coffees. Meanwhile, lipids, lactic acid, and 5-caffeoylquinic acid were found as characteristic metabolites for Aceh Robusta coffee. This report provided knowledge about the chemical composition of Lampung and Aceh Robusta coffees and shed more light on the diversity of Indonesian Robusta coffees. Furthermore, it confirmed that 1H NMR analysis coupled with chemometrics was a powerful method for evaluating and classifying metabolite profiles of the roasted Robusta coffees.